2007
DOI: 10.1111/j.1365-2656.2007.01227.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and interspecific density‐dependent dispersal in an aquatic prey–predator system

Abstract: Summary1. Dispersal intensity is a key process for the persistence of prey-predator metacommunities. Consequently, knowledge of the ecological mechanisms of dispersal is fundamental to understanding the dynamics of these communities. Dispersal is often considered to occur at a constant per capita rate; however, some experiments demonstrated that dispersal may be a function of local species density. 2. Here we use aquatic experimental microcosms under controlled conditions to explore intra-and interspecific den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 49 publications
(81 reference statements)
1
68
0
Order By: Relevance
“…Predator-prey models based on demographic processes typically assume instantaneous and density-independent movement (Jansen 2001) on the same time scale as demographics. In contrast, predator avoidance or foraging behavior can trigger densitydependent movement on much faster timescales (Abdllaoui et al 2007;Hauzy et al 2007). In particular, the time to movement from a patch can be comparable to travel time between patches.…”
Section: Density-dependent Dispersal and Timescales Of Movementmentioning
confidence: 96%
“…Predator-prey models based on demographic processes typically assume instantaneous and density-independent movement (Jansen 2001) on the same time scale as demographics. In contrast, predator avoidance or foraging behavior can trigger densitydependent movement on much faster timescales (Abdllaoui et al 2007;Hauzy et al 2007). In particular, the time to movement from a patch can be comparable to travel time between patches.…”
Section: Density-dependent Dispersal and Timescales Of Movementmentioning
confidence: 96%
“…As a matter of fact, more and more researchers find that the dispersal rates of populations should be affected by many other factors such as the qualities and quantities of foods, the pressures from competitors and the predation risks of enemies. For example, Hauzy et al [7] observed that the dispersal of prey is influenced by its own density and predators' density, and the dispersal rate of predators is affected by prey's density. de Roos et al [6] and Persson et al [14] studied flexible behaviors in size-structured populations by assuming that the movement rate out of a patch is purely a function of fitness of individuals within that patch.…”
mentioning
confidence: 98%
“…In the majority of cases (Hassell 1971;Bernstein 1984;Kratz 1996;Maeda et al 1998;Zemek and Nachman 1998;Diehl et al 2000;French and Travis 2001;Hauzy et al 2007;Ohara and Takabayashi 2012), were the strength of the observed density dependence within the range for which our covariance approximation is accurate.…”
Section: Empirical Emigration-rate Responsesmentioning
confidence: 71%